1997
DOI: 10.1007/bf02406064
|View full text |Cite
|
Sign up to set email alerts
|

A new high-pressure squeezing technique for pore fluid extraction from terrestrial soils

Abstract: Abstract. A new plastic-lined high-pressure squeezing device has been developed for the extraction of soil pore solutions. At a maximum pressure of 1100 kg cm -~" the water recovery ranged between 30 and 55% of the total water content. Pressure dependent squeezing experiments showed a general increase in Si, Mn, Mg, Ca, K, Na, AI, Fe, Cd, and Zn concentrations with progressive pore water extraction and increasing pressure, indicating that micro pore solutes have the highest concentrations of solutes. Soil samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 6 publications
1
22
0
2
Order By: Relevance
“…Further, soil water isotopic composition can be determined via direct equilibration techniques. Laboratory methods include: azeotropic distillation (Revesz and Woods, 1990;Thorburn et al, 1993), microdistillation (Kendall and Coplen, 1985), mechanical squeezing (Böttcher et al, 1997;Wershaw et al, 1966;White et al, 1985), cryogenic vacuum extraction (Dalton, 1988;Goebel and Lascano, 2012;Orlowski et al, 2013;Dawson and Ehleringer, 1993;West et al, 2006;Ehleringer et al, 2000), a modified vacuum extraction technique (Koeniger et al, 2011), centrifugation with or without immiscible heavy liquids (Mubarak and Olsen, 1976;Batley and Giles, 1979;Barrow and Whelan, 1980;Peters and Yakir, 2008), Picarro's Induction Module (Picarro, 2015), microwave extraction (Munksgaard et al, 2014), or the accelerated solvent extraction technique (Zhu et al, 2014). Field-based methods include: wick samplers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Further, soil water isotopic composition can be determined via direct equilibration techniques. Laboratory methods include: azeotropic distillation (Revesz and Woods, 1990;Thorburn et al, 1993), microdistillation (Kendall and Coplen, 1985), mechanical squeezing (Böttcher et al, 1997;Wershaw et al, 1966;White et al, 1985), cryogenic vacuum extraction (Dalton, 1988;Goebel and Lascano, 2012;Orlowski et al, 2013;Dawson and Ehleringer, 1993;West et al, 2006;Ehleringer et al, 2000), a modified vacuum extraction technique (Koeniger et al, 2011), centrifugation with or without immiscible heavy liquids (Mubarak and Olsen, 1976;Batley and Giles, 1979;Barrow and Whelan, 1980;Peters and Yakir, 2008), Picarro's Induction Module (Picarro, 2015), microwave extraction (Munksgaard et al, 2014), or the accelerated solvent extraction technique (Zhu et al, 2014). Field-based methods include: wick samplers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The connections between the top and bottom endplates and the Inox chamber were sealed with O-rings. Böttcher et al [42] suggested that porewater chemistry could be modified when pressures were as high as 60 MPa due to the collapse of soil structures. Thus, this method is considered suitable for fine-grained and organic-matter-sediments [41].…”
Section: Porewater Extraction Methodmentioning
confidence: 99%
“…This method is cumbersome and, in addition, suitable equipment is not as widely available as centrifuges. Yet, likewise, an increase in the concentrations of practically all the chemical constituents with progressive pore water extraction is reported (Böttcher et al 1997). In both the centrifugation and the pressure squeezing extraction techniques, the removal of the liquid phase is never complete because some of the liquid stays in the sediment.…”
Section: Introductionmentioning
confidence: 95%
“…Here, too, changes in chemical composition are exhibited during progressive extractions. The second method is extraction of pore fluids by high-pressure squeezing (Böttcher et al 1997). This method is cumbersome and, in addition, suitable equipment is not as widely available as centrifuges.…”
Section: Introductionmentioning
confidence: 99%